An Efficient Downlink Mapping Algorithm for AMC Mode in WiMAX Systems - Lee, Tsern-Huei; Yang, Zi-Yang; Huang, Qi-Quan; Kuo, Yaw-Wen (My University, 2012)
This paper proposes an efficient downlink resource allocation scheme for Orthogonal Frequency Division Multiple Access based WiMAX systems using the Adaptive Modulation and Coding mode operation. Given a set of user requests, the proposed algorithm determines the modulation scheme and allocates a two-dimensional (time and frequency) burst to each user. It is known that finding the optimal solution for such a resource allocation problem is NP-complete. To reduce the computation complexity, this paper proposes a heuristic solution. Compared with the Efficient Downlink Bandwidth Allocation (EDBA) algorithm [6], the proposed scheme achieves higher channel utilization and system throughput with similar execution time. Simulation results show that the average channel utilization of the proposed scheme is about 75 similar to 85% and that of EDBA is about 60 similar to 70%.
Keywords: OFDMA; WiMAX; Burst mapping; AMC